Design and Development of Automatic Seed Sowing Machine - Premalatha, P.; Singh, Sharath (Asian Journal of Electrical Sciences, 2019)
Indian economy is dependent on agriculture to a great extent. Increase in production, tends to improve social welfare, particularly in rural areas. This project aims to increase the productivity and to reduce the time for seed sowing process and wastage of seeds. Automatic seed sowing machine designed and developed, which uses Solar powered DC motors driven by L298N driver circuit with Aurdino UNO R3 control kit. An ultrasonic sensor is also installed to detect the obstacle in the path and end of each row.